Digital and Nurse-Led Telecounseling Interventions to Enhance Breastfeeding Self-Efficacy: A Scoping Review - Nurrachma Ariestanti; Sri Hendrawati; Henny Suzana Mediani (Media Publikasi Cendekia Indonesia, 2026)
Breastfeeding self-efficacy plays a vital role in determining breastfeeding success, yet many mothers face challenges in accessing timely support after childbirth. Nurses hold a key position in providing breastfeeding counseling, and digital technology enables them to deliver care more effectively to a wider population. This scoping review aims to explore and describe the current evidence on nurse-led telecounseling, and digital interventions designed to improve breastfeeding self-efficacy. The review followed the Joanna Briggs Institute (JBI) methodology and PRISMA-ScR reporting guidelines. Articles were identified from PubMed, Scopus, ScienceDirect, SAGE Journals, and Google Scholar, focusing on English-language studies published between 2015 and 2025. Eligible studies included nurse-led digital counseling programs or telecounseling interventions targeting breastfeeding mothers with infants aged 0–6 months. A total of 515 articles were screened, 12 met the inclusion criteria. Most studies used quasi-experimental and randomized controlled trial designs. The results indicated that nurse-led interventions delivered through phone calls, messaging applications, and mobile health platforms significantly improved breastfeeding self-efficacy. Proactive and continuous interventions were found to be more effective than reactive approaches, particularly when the support was interactive and structured. Overall, nurse-led digital and remote counseling interventions effectively enhanced maternal confidence in breastfeeding by providing education, emotional support, and therapeutic communication. The integration of digital health technology in nursing practice can expand access to consistent, high-quality breastfeeding support services, especially for mothers living in areas with limited healthcare access.